Sibeveyhi’nin el-Kitab’ı çerçevesinde dil çalışmalarının doğuşu - Benli, Ali (My University, 2007)
Elimize ulaşan ilk Arapça gramer eseri olan el-Kitâb, Sîbeveyhi (ö. 180/ 796) tarafından sekizinci asırda Basra şehrinde telif edilmiştir. Bu eser fasih Arapçanın tasvir ve tahlilini ihtiva ettiği gibi bazı dilbilim teori ve kavramlarını da haizdir. Sîbeveyhi’nin Arap dilini tahlili temelde şu üç kaynağa dayanmaktadır: Kur’ân metni, eski Arap şiiri ve dilleri bozulmamış bedevilerin konuşmaları. Arap diline dair bilimsel çalışmaların veya başka bir deyişle Arap gramerinin başlangıç dönemine dair elimizdeki en erken kaynak Sîbeveyhi’nin eseri el-Kitâb’tır. Bu döneme dair geleneksel açıklama tarzı, Arap gramerinin başlangıcını Ebu’l-Esved ed-Düelî’ye götürmekte ve bunu dilin bozulması, lahnin artması ve Kur’ân kıraatine yansıması üzerine Kur’ân’ı bu tür hatalardan koruma amacı ile gerçekleştirildiğini bildirmektedir. Ebu’l-Esved ile başlayan dilbilim geleneği Sîbeveyhi’ye kadar devam etmiş ve Sîbeveyhi’nin el-Kitâb’ı telif etmesiyle en büyük semeresini vermiştir. Bu çalışmada Ebu’l-Esved’den başlayıp Sîbeveyhi’ye kadar devam eden bu geleneğin el-Kitâb’taki izleri kendilerinden yapılan nakiller muvacahesinde takip edilmekte ve böylece dönem el-Kitâb perspektifinden ele alınmaktadır. Ayrıca Arap dilbilimin doğuşu konusundaki yabancı etkisi iddiaları ele alınmış ve meselenin sosyal ve dini etkenleri bahis konusu yapılmıştır.

The first Arabic grammar known to us is al-Kitāb, composed by Sībawayhi (d. 180/ 796) in the eighth century in the city of Basra. It contains a description and analysis of the old Arabic language (al-fousha) as well as some linguistic theories and notions. Sībawayhi’s description and analysis of Arabic based on three main sources: The text of Kur’ān, ancient Arabic poetry and the ordinary speech of some native speakers. The only reliable source of information about rise of Arabic linguistic studies or what we might call primitive grammar is al-Kitāb itself. The traditional narrative ascribing the invention of grammar to Abu’l-Aswad al-Du’alī, thence through generations of scolars up to and Sībawayhi, has an inner coherence which corresponds well to likely stages in the growth of linguistic consciousness, responding to the increasing volatility of Arabic and the need for a definitive form of the text upon which the new Islamic civilization now depended. In this work, we examined evidences of this philological tradition in Sībawayhi’s al-Kitāb and the attemps to trace the origins of Arabic grammar to external influences, principally Greek, via Syriac. Abstract The first Arabic grammar known to us is al-Kitāb, composed by Sībawayhi (d. 180/ 796) in the eighth century in the city of Basra. It contains a description and analysis of the old Arabic language (al-fousha) as well as some linguistic theories and notions. Sībawayhi’s description and analysis of Arabic based on three main sources: The text of Kur’ān, ancient Arabic poetry and the ordinary speech of some native speakers. The only reliable source of information about rise of Arabic linguistic studies or what we might call primitive grammar is al-Kitāb itself. The traditional narrative ascribing the invention of grammar to Abu’l-Aswad al-Du’alī, thence through generations of scolars up to and Sībawayhi, has an inner coherence which corresponds well to likely stages in the growth of linguistic consciousness, responding to the increasing volatility of Arabic and the need for a definitive form of the text upon which the new Islamic civilization now depended. In this work, we examined evidences of this philological tradition in Sībawayhi’s al-Kitāb and the attemps to trace the origins of Arabic grammar to external influences, principally Greek, via Syriac.
Keywords: Arap Dili; İslam Dini